Konseling tentang Spinal Anestesi untuk Meningkatkan Pengetahuan Pasien Pasca Spinal Anestesi - Marthunus Judin; Suhadi Suhadi (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2022)
This community service aims to improve patient knowledge after spinal anesthesia through structured counseling activities. Spinal anesthesia often causes anxiety and is dangerous for patients, especially related to side effects and the recovery process. Lack of understanding can lead to non-compliance with medical injuries, which has the potential to prolong the recovery period and increase risk complications. Therefore, counseling is carried out by providing direct education to patients and families using educational media such as leaflets and interactive discussions. This approach not only helps improve patient understanding of spinal anesthesia procedures but also plays a role in reducing anxiety and increasing compliance with postoperative care. The results of the activity showed a significant increase in the level of patient knowledge, which has an impact on a better recovery experience. Thus, this counseling program contributes to improving the quality of health services and patient satisfaction at PKU Muhammadiyah Surakarta Hospital, as well as being a model of educational intervention that can be applied in various other health facilities.